1996
DOI: 10.1007/bf01329237
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in the crystallization of Ti-Ni-SC system alloys in the TiNi - Ni - ScNi region

Abstract: 699.017.3.24'295'793'The Ti-Ni-Sc diagram has been examined for nickel contents of 50-100 at. %. The alloys were prepared by arc melting and were examined by metallography, differential thermal analysis, and microprobe analysis. There are four nonvariant equilibria: two incongruent ones and two congruent ones. The minimum melting point of 980°C occurs in alloys with the base composition (TiNi3) + (ScNi2) + (TiNi), which form a eutectic.Nothing has been published on component interaction in the ternary Ti-Ni-Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Sc-Ni-Ti ternary system has been investigated by Semenova and Velikanova using PXRD, EPMA and DSC. [110][111][112] It has been reported that the ternary system can be triangulated along the quasi-binary section The ternary Rh-Ru-Sc system has been investigated in detail by Kornienko and co-authors using PXRD, EMPA and DSC techniques. 113 No ternary compounds were found.…”
Section: Scniti Rhscti and Rhruscmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sc-Ni-Ti ternary system has been investigated by Semenova and Velikanova using PXRD, EPMA and DSC. [110][111][112] It has been reported that the ternary system can be triangulated along the quasi-binary section The ternary Rh-Ru-Sc system has been investigated in detail by Kornienko and co-authors using PXRD, EMPA and DSC techniques. 113 No ternary compounds were found.…”
Section: Scniti Rhscti and Rhruscmentioning
confidence: 99%
“…The Sc-Ni-Ti ternary system has been investigated by Semenova and Velikanova using powder X-Ray diffraction (PXRD), Electron Probe Micro-Analysis (EPMA), and differential scanning calorimetry (DSC). [110][111][112] It has been reported that the ternary system can be triangulated along the quasi-binary section TiNi−Sc 0. The ternary Rh−Ru−Sc system has been investigated in detail by Kornienko et al 113 using PXRD, EMPA and DSC techniques.…”
Section: Sc−ni−ti Rh−sc−ti and Rh−ru−scmentioning
confidence: 99%
See 1 more Smart Citation